A DISCOURSE ANALYSIS OF JOB ADVERTISEMENTS IN ENGLISH AND VIETNAMESE - Assoc. Prof. Dr. Lưu Quý Khương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This is a discourse analysis of job advertisements in English and Vietnamese. The data for analysis in this thesis are 200 samples of job advertisements (100 in English and 100 in Vietnamese) collected from popular and prestigious online newspapers in the United States, the United Kingdom and Vietnam. The research is carried out based on the combination of a variety of methods, namely qualitative, quantitative, statistics, descriptive, analytic, synthetic, comparative, contrastive, and inductive. The study analyzes discourse features of English and Vietnamese job advertisements in terms of discourse structure, grammatical features, lexical features and cohesive devices. It also makes a comparison to discover the similarities and differences of these features between the two languages.